Harsh parenting and child brain morphology: a population-based study - Cortes Hidalgo, Andrea P. (Child maltreatment, 2022)
Evidence suggests that maltreatment shapes the child’s brain. Little is known, however, about how normal variation in parenting influences the child neurodevelopment. We examined whether harsh parenting is associated with the brain morphology in 2,410 children from a population-based cohort. Mothers and fathers independently reported harsh parenting at child age 3 years. Structural and diffusion-weighted brain morphological measures were acquired with MRI scans at age 10 years. We explored whether associations between parenting and brain morphology were explained by co-occurring adversities, and whether there was a joint effect of both parents’ harsh parenting. Maternal harsh parenting was associated with smaller total gray (β = −0.05 (95%CI = −0.08; −0.01)), cerebral white matter and amygdala volumes (β = −0.04 (95%CI = −0.07; 0)). These associations were also observed with the combined harsh parenting measure and were robust to the adjustment for multiple confounding factors. Similar associations, although non-significant, were found between paternal parenting and these brain outcomes. Maternal and paternal harsh parenting were not associated with the hippocampus or the white matter microstructural metrics. We found a long-term association between harsh parenting and the global brain and amygdala volumes in preadolescents, suggesting that adverse rearing environments common in the general population are related to child brain morphology.